Awareness among professionals in malaysian construction industries on reinforcement corrosion prevention and protection - Ismail, Mohammad; Mohamad Zin, Rosli; Ismail, Mohamed A.; Mohd. Yatim, Jamaluddin; Omar, Wahid (Faculty of Civil Engineering, 2008)
Reinforced concrete structures are subjected to damage and deterioration during their service life because of exposure to many types of environmental influence. These damages or deterioration can reduce the performance and intended function of the structure. On several occasions structural failures are closely linked to the corrosion of steel reinforcement in concrete. Information about the current practice to prevent and protect corrosion of reinforcement in Malaysia is fragmented and hard to acquire. Local standard for corrosion treatment technique is not available. Each concrete repair organizations normally have their own approaches in solving corrosion problems. This has made it difficult for regulatory agencies to plan and implement an effective corrosion management system in the country. This paper presents the results of an industry survey concerning the awareness of local professionals toward reinforcement corrosion protection and prevention. The respondents were professionals working with consultants, contractors, suppliers and research institutions. The results indicate that common methods of corrosion prevention are surface treatment and improvement in concrete technology, while patch repair and chloride removal are frequently used for treating corrosion. In general, the level of awareness among professionals on common methods of corrosion protection and prevention is considered satisfactory. However the awareness on modern and high technology methods in treating corrosion are still weak and need to be enhanced. The solar energy approach in preventing and protecting reinforcement corrosion was not implemented in Malaysia.